Cost-Benefit Analysis in Jatropha Curcas Plantation of Rural Farmers under Shared Benefits Business with Investor - Nawalertpanya, Khumthorn; Thanarak, Prapita; Ketjoy, Nipon (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 1 (2014): January-April 2014, 2014)
This research paper focuses on the investigation of a new system of Jatropha plantation for crude oil production under shared benefits business with investor, which could serve a large scale of Jatropha crude oil production in Thailand. The business functions between farmers and investor can be divided in 7 steps. Only 3 steps as plantation, harvesting and delivery to collecting center are managed by farmers, other 4 steps as nursery, transport to factory, crude oil production and shipping to end customers by investor. With agreements to support Jatropha farmers by providing them know-how and raw materials such as seedings, fertilizers or pesticides, etc., they both would reach the highest return. The Jatropha plantation models are analyzed by plantation scales of 1-1,000 rai (1 rai equals to 1,600 m2), planning technique of 250 seedings/rai, various quantity of fertilizer and pesticide, Jatropha yielding time of 25 years, various seeds prices and seed yields. All costs and incomes of farmers are considered and economically analyzed with helps of economic tools as Net Present Value (NPV) and return on investment (ROI). The results showed that, without helps from investor, Jatropha plantation could be beneficial when plantation scale starts from 5 rai and minimum seeds price at 9 baht/kg, while under shared benefits business at only 6 baht/kg. The shared benefit business makes Jatropha cultivation of 20 rai or over by the lowest seeds price of 3 baht/kg also beneficial. Keywords:  Jatropha Curcas, Cost-Benefit Analysis, Rural Farmer
Keywords: Jatropha Curcas, Cost-Benefit Analysis, Rural Farmer